A brief overview of spray drying technology and its potential in food applications - Kumoro, Andri Cahyo; Wardhani, Dyah Hesti; Kusworo, Tutuk Djoko; Djaeni, Mohammad; Ping, Tan Chin; Alhanif, Misbahudin (Ital Publication, 2024)
Spray drying is one of the most preferred preservation methods that converts an aqueous feed containing solvent, carrier agent, and food compounds into dry powder with superb physicochemical and functional properties. This paper reviews the fundamental and important operating parameters, product characteristics, current and potential applications, and techno-economic aspects of spray drying. The key operating parameters should be chosen to achieve the highest spray drying performance in terms of operational efficiency and product quality. A successful spray drying operation is greatly dependent on the feed material properties, the mechanical design of the equipment, and selected operating parameters. This paper also found that water content, water activity, and glass transition temperature are the main parameters that really determine product quality in terms of shelf life and storage conditions of food powder obtained from the spray drying process. Recent advances in the development of new heatless spray drying technology in the manufacture of food flavoring and nutraceuticals are interesting to develop, in addition to the potential to produce nano-sized powders with distinctive properties and the use of superheated steam and carbon dioxide to sterilize products. The appropriate information on spray drying technology featured in this paper is targeted to reinforce researcher and practitioner understanding for widening its applications in pertinent food industries